The Kitchen Table: Alternative Perspectives on Program Planning - Shauna Butterwick; Thomas J. Sork (Adult Education Research Conference, 2010)
The literature on program planning in adult education has been dominated by the technical-rational perspectives of a largely white, male, North American group of scholars. We note why this gap is problematic for the field and introduce a new generative metaphor, the kitchen table. This metaphor opens up a space for deliberation about aesthetic and feminist considerations, as well as directing attention to non-Western approaches, particularly ideas about community collaboration from an Indigenous perspective